NILAI-NILAI ISLAM DALAM BUDAYA DAN KEARIFAN LOKAL (Konteks Budaya Minangkabau) - Kori Lilie Muslim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2017)
This paper aims to analyze the influence of Islamic values in Indonesia in the form of culture and local wisdom of the Minangkabau people. We will discover the extraordinary fact that Minangkabau local culture and wisdom has a very high Islamic value. Culture is something very important in society, because culture is identity. Culture makes a society different from another society. In society, culture has its own value, just like the Arabic culture and Indonesian culture. The different from Arabic culture and Indonesian culture is influenced by desert. The arabic live in difficult way whereas the Indonesian live in prosperous area. The prosperous area. will create an extraordinary culture. Besides, the local wisdom in Indonesia is influenced by the sharia value. That is because of Islam has become the majority that affects everyone in Indonesia, espe cially Minangkabau people. The presence of Islam in Malay brought new concepts and values that replace the mystical values toward rational thinking. Islam also capable in solving unresolved problems in previous Malay beliefs. The deep influence makes Malay culture identicl with Islam. This is due to the proverb mention “